2022
DOI: 10.1007/s10461-022-03617-5
|View full text |Cite
|
Sign up to set email alerts
|

Adherence, Sexual Behavior and Sexually Transmitted Infections in a New Zealand Prospective PrEP Cohort: 12 Months Follow-up and Ethnic Disparities

Abstract: Inequities in pre-exposure prophylaxis (PrEP) experiences will impede HIV epidemic elimination among gay and bisexual men (GBM). Ethnicity is a strong marker of inequity in the United States, but evidence from other countries is lacking. We investigated experiences on-PrEP to 12 months follow-up in a prospective cohort of 150 GBM in Auckland, New Zealand with an equity quota of 50% non-Europeans. Retention at 12 months was 85.9%, lower among Māori/Pacific (75.6%) than non-Māori/Pacific participants (90.1%). Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 75 publications
1
6
0
Order By: Relevance
“…1). Finally, 20 studies met the inclusion criteria for the final analysis 11–30 . From these studies, we extracted 19 groups of incidence data of syphilis, 19 of gonorrhea, and 18 of chlamydia infection during the PrEP period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Finally, 20 studies met the inclusion criteria for the final analysis 11–30 . From these studies, we extracted 19 groups of incidence data of syphilis, 19 of gonorrhea, and 18 of chlamydia infection during the PrEP period.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 20 studies met the inclusion criteria for the final analysis. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] From these studies, we extracted 19 groups of incidence data of syphilis, 19 of gonorrhea, and 18 of chlamydia infection during the PrEP period. Five of these studies investigated the incidence data before taking PrEP.…”
Section: Results Literature Collectionmentioning
confidence: 99%
“…Consistent with previous studies, 3,21 MSM experienced higher odds of gonorrhea reinfection, which typically reflects higher gonorrhea and syphilis rates experienced by this group 2 . Exposure to STIs for MSM is increased by behavioral and network factors (i.e., higher number of partners, partner concurrency) 43s,44s and a higher underlying prevalence of gonorrhea and syphilis in MSM communities 29 . 45s A notable limitation in the present study is that sexual behavior data for reported gonorrhea cases since 2018 are still incomplete, with up to 50% of cases without any supplemental sexual behavior data provided, and an additional 25% reported as “other” by reporting clinicians (including unknown behavior).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the higher rates of gonorrhea reinfection among males, including MSM, may reflect higher rates of symptomatic gonorrhea and chlamydia, prompting rescreening, or asymptomatic screening for PrEP use, 27 important in an NZ context because PrEP became fully funded in 2018 and up to 19% of MSM are on PrEP 28 . Specifically, prior STI and condomless sex are indicators for PrEP, PrEP users have high STI incidence, and quarterly screening of PrEP users increases detection bias for STIs 29 . 31s Factors such as age, sex, HIV status, and PrEP use are potentially proxies for higher rates of partner change and/or sexual networks with higher underlying prevalence of undiagnosed STIs.…”
mentioning
confidence: 99%
“…Structural factors that plausibly shape and enable chemsex in NZ, such as population size and the role of tourism and travel, should also be considered. Auckland has a much smaller population than comparative gay meccas of London, Sydney and Berlin [9], likely without the critical mass of GBM to organise and sustain regular chemsex sessions. GBM in NZ might therefore travel to engage in chemsex [31,32], or local practices of chemsex could be shaped by those visiting NZ.…”
Section: Contemplating Chemsex As a Specific Subset Of Sexualised Dru...mentioning
confidence: 99%